Extracting knowledge from ontology using Jena for semantic web - Ameen, Ayesha; Khan, Khaleel Ur Rahman; Rani, B. Padmaja (International Conference for Convergence for Technology-2014, 2014)
Semantic Web extends the current web by standardizing the semantics. Purpose of Semantic Web is to make people share data and content among different applications. This is made possible by using ontologies which represents shared understanding of a domain. Semantic Web uses ontologies for representing knowledge in a uniform way that can be easily processed and shared among machine. This paper gives detail description of the role of ontologies in Semantic Web and tools required for constructing Semantic Web applications. An application is created which loads the ontology created in Protégé into Eclipse and displays the properties and classes of ontology.